Identification and characterization of a new and distinct molecular subtype of human T-cell lymphotropic virus type 2. - Eiraku, N (1996)
Molecular studies have demonstrated the existence of at least two major subtypes of human T-cell lymphotropic virus type 2 (HTLV-2), designated HTLV-2a and HTLV-2b. To further investigate the heterogeneity of this family of viruses, we have characterized the HTLV-2 subtypes present in several urban areas in Brazil. DNAs from peripheral blood mononuclear cells of a large number of infected individuals, the majority of whom were intravenous drug abusers, were analyzed by using PCR with restriction fragment length polymorphism and nucleotide sequencing analysis. Restriction fragment length polymorphism analysis of the env region suggested that all individuals were infected with the HTLV-2a subtype, and this was confirmed by nucleotide sequence analysis. In contrast, nucleotide sequence analysis of the long terminal repeat demonstrated that although the viruses were more related to the HTLV-2a than to the HTLV-2b subtype, they clustered in a distinct phylogenetic group, suggesting that they may represent a new and distinct molecular subtype of HTLV-2. This conclusion was supported by nucleotide sequence analysis of the pX region, which demonstrated that the Tax proteins of the Brazilian viruses differed from that of prototype HTLV-2a isolates but were more similar to that of HTLV-2b in that they would be expected to have an additional 25 amino acids at the carboxy terminus. In transient expression assays, the extended Tax protein of the prototype HTLV-2a subtype. The studies suggest that the Brazilian viruses analyzed in this study, while being phylogenetically related to the prototypic HTLV-2a seen in North America, are phenotypically more related to HTLV-2b and can be justifiably classified as a new molecular subtype, which has been tentatively designated HTLV-2c.